PROFIL KEMAMPUAN SISWA SMP NEGERI 3 POSO PESISIR UTARA DALAM MENYELESAIKAN SOAL CERITA TENTANG LUAS PERMUKAAN DAN VOLUME LIMAS BERDASARKAN ADVERSITY QUOTIENT - Mang Megayanti; Baharuddin Paloloang; Ibnu Hadjar (Universitas Tadulako, 2022)
The purpose of this study was to obtain a description of the ability profile of students of SMP Negeri 3 Poso Pesisir Utara class VIIIC in solving story problems about the surface area and volume of pyramids based on Adversity Quotient (AQ). This study used descriptive qualitative method. Based on the results of data analysis, it was found that: (1) CB subjects were able to understand problems, plan solutions, implement settlement plans and re-examine problem solving. CB subjects are able to mention things that are known and asked correctly, are able to express the steps for solving and solving problems according to the plan properly, and re-examine the results of the completion. (2) CP subjects are able to understand the problem, namely being able to mention things that are known and asked correctly. In addition to planning a solution, the CP subject is also able to carry out the settlement plan that he has planned in solving the problem, but does not re-examine the solution because he feels confident with the answer. (3) QT subjects are able to understand the problem, namely being able to mention things that are known and asked correctly. QT subjects also plan solutions, but in carrying out the settlement plans, QT subjects do not solve the problem completely, because they already find it difficult and confused to continue working on the problem. QT subjects also did not re-examine their answers.